Formulation and Characterization of Felodipine as an Oral Nanoemulsions - Sumaya B. Hamed; Shaimaa N. Abd Alhammid (College of Pharmacy University of Baghdad, 2021)
Felodipine is a calcium-channel blocker with low aqueous solubility and bioavailability. Lipid dosage forms are attractive delivery systems for such hydrophobic drug molecules. Nanoemulsion (NE) is one of the popular methods that has been used to solve the dispersibility problems of many drugs. Felodipine was formulated as a NE utilizing oleic acid as an oil phase, tween 80 and tween 60 as surfactants and ethanol as a co-surfactant. Eight formulas were prepared, and different tests were performed to ensure the stability of the NEs, such as particle size, polydispersity index, zeta potential, dilution test, drug content, viscosity and in-vitro drug release. Results of characterization showed that felodipine nanoemulsion (F3) with (oleic acid 10%) ,(Smix 60% of tween80 :ethanol in a ratio of 3:1), (DDW 30%) was selected as the best formula, since it has a particle size of (17.01)nm, low PDI (0.392), zeta potential (-22.34mV), good dilution without drug precipitation , higher percent of drug content (99.098%) with  acceptable viscosity , and complete release of the drug after (45 min.) with significantly higher (P<0.05)   dissolution  rate in comparison with the pure drug powder. The selected formula (F3) subjected to further investigations as drug and excipient compatibility study by Fourier transform infrared spectroscopy (FTIR) The outcomes of the (FTIR) explain that the distinctive peaks for felodipine were not affected by other components and displayed the same functional group's band with very slight shifting. This indicates that there was no interaction between felodipine and other NE components. Therefore, these excipients were found to be compatible with felodipine. In conclusion, the NE was found to be an efficient method to enhance the dispersibility and permeatioins of drugs that have poor water solubility (lipophilic drugs).